Pulsed Corona Discharge in Water Treatment: The Effect of Hydrodynamic Conditions on Oxidation Energy Efficiency; Industrial & Engineering Chemistry Research; Vol. 54 (30) - Ajo P. Petri (2015, 2015)
Title screen